Smallholders’ willingness to pay for ZM-GrowTM foliar fertilizer in Dangla District of Northwestern Ethiopia - Zewdu, Tadele Anagaw; Wassie, Solomon Bizuayehu; Tesfaye Teferi, Ermias (Informa UK Limited, 2024)
Using primary data collected from 389 sample households in Dangla district, Amhara region of Ethiopia, this study examined smallholder farmers’ willingness to pay for ZM-GrowTM foliar fertiliser. The study employed the Tobit model to estimate the determinants of the maximum willingness to pay and a seemingly unrelated bivariate probit model to estimate the mean willingness to pay for foliar fertiliser. The results of the Tobit regression model showed that the education level of the farm household, total annual income, access to credit service, access to agricultural extension service, perception about fertiliser, and cost of the existing fertiliser have a positive and significant effect on farm households’ willingness to pay. On the other hand, the age of farm households, availability of labour, and initial bid price have negative and significant effect on farm households’ willingness to pay for ZM-GrowTM foliar fertiliser. The mean willingness to pay for ZM-GrowTM foliar fertiliser, estimated using the seemingly unrelated bivariate probit model, was 121.16 birr/litre (2.75 USD/litre). The corresponding mean willingness to pay amount estimated from an open-ended format was 161.105 Birr/litre (3.65 USD/litre). The results suggest that foliar fertilisers could be good alternatives to the existing fertilisers and its adoption can be further facilitated through improved access to knowledge and finance/credit.